Why Jesus?. (September 2014) - Cobb, John B.
Abstract Jesus plays potentially a uniquely important role in relation to the world's greatest needs. To respond to the global crisis, we need historical consciousness. The source of historical consciousness is the prophetic tradition. Through Jesus the prophetic tradition became widely available and important. However, this consciousness has been responsible for great evil as well as great good, often bound up with we/they thinking and the use of violence. Jesus' teaching of love of the enemy in principle overcomes this tendency and points to way forward.